Measures used in assessing outcomes of school‐wide positive behaviour support. Issue 4 (18th September 2012) - Brandt, Rachel C.; Chitiyo, Morgan; May, Michael E.
<x xml:space="preserve">Abstract</x> School‐Wide Positive Behaviour Support (SWPBS) is increasingly becoming a popular approach to managing challenging behaviour in schools. However, several issues still have to be addressed facilitate successful implementation of this approach in schools. One of these issues pertains to the appropriateness of the different measures used to determine the efficacy of the approach. Because many schools are using indirect measures to assess the effects of SWPBS implementation, determining which measures more accurately reflect the effectiveness of the SWPBS components may increase the effectiveness of school measurement systems. The purpose of this study was to examine the measures used in evaluating the efficacy of positive behaviour support. The paper discusses the strengths and weaknesses of outcome measures regarding problem behaviour, prosocial behaviour, and implementation fidelity.